Supply chain collaboration - Guy Rodrigue Ghomsi 1982- (2015)
Companies are now progressively looking beyond themselves to come up with ways to improve revenue and profit margins. This has resulted in a heightened focus on the efficiency of the supply chains. Inefficient supply chains are being perceived as cavities that can deprive the firm from its cash flows when inventory is not required and sales revenue when product is not available at the point of sales. This has stimulated development of business models that intend to leverage and enhance the supply chain management. This resulted in supply chain collaboration. Supply chain collaboration made sense as the conventional supply chain models have their inherited issues like unfamiliar customer expectations and costs and efficiency concerns and suppliers together can provide a much superior customer service to the customers. Collaboration of supply chain can be understood as the sharing of mutual objectives; a sense of commitment; trust and respect; skills and knowledge; and intellectual alertness. Presently there are not many studies dedicated to understanding the need for or analyzing the present scenario of collaborative supply chain management in the manufacturing industry of Iceland. Therefore this study is an attempt at bridging this research gap. It was found that the collaborative supply chain in the manufacturing industry in Iceland was under-mined. Though most firms have adopted the practice but there are many explicit and implicit barriers confronting the progression. Suitable recommendations are made on the basis of the empirical study conducted.